Developing a High Value Timber Industry in the Leyte Based on Furniture Production: Future Prospects and Lessons from Experiences in Tropical Australia - Herbohn, John; Harrison, Steve; Smorfitt, David (Annals of Tropical Research, 2003)
The desirability of and prospects for development of a high-value timber industry in Leyte, Philippines, are examined. Lessons are drawn from extensive research undertaken in tropical north Queensland, Australia, including studies of landholder attitudes; sawmilling activities, including the role of portable sawmills; potential financial returns from plantations of high value rainforest cabinet timbers; and marketing studies involving cabinet-makers and consumers. These studies suggest the need to demonstrate that money can be made from smallholder and community plantations, to have harvest security, to convince politicians and public about benefits of forestry, to be able to develop effective programs that target particular groups, and to develop a range of financing arrangements (e.g. carbon credits, institutional and venture capital) that allow early cash flows. Issues associated with the development of a furniture industry in the Leyte are discussed in the light of these research experiences.